Beta blockers in the perioperative period. (2nd February 2020) - Prince, Mark
Abstract : The cardiovascular effects of beta blockers are widespread, so their use in the perioperative period ought to be beneficial, although this is not clear cut. This article discusses the evidence for and against the use of beta blockers perioperatively and gives guidance for best practice.